Conflito, argumento e negociação : San Tiago Dantas e a Conferência de Punta Del Este, 1962 - Azevedo, Arthur Schreiber de (2014)
This dissertation deals with the actions of the Brazilian Chancellor San Tiago during the negotiations of the Punta del Este Conference, 1962. It aims understand a conceptual change in Brazil's international insertion during this negotiation, changing from Pan-Americanism, which prescribed a priority relation with the United States and with inter-American system, for the neutralism and/or Latin Americanism, which prescribed the universalization of these relations globally, and also the deepening relationship between the underdeveloped countries of the continent. The dissertation concludes that, initially, Dantas intended to prevent the convening of the Conference because it could cause negative innovations in the functioning of the Inter-American system, incorporating harmful aspects of the cold war. He elaborated, with this objective, a plan of neutralization of Cuba to isolate it from that influence system, favoring the regional rather than global. However, as their strategies failed, the Brazilian Chancellor changed its initial position, prescribing that the Cuban case should be treated as an event of the dynamics of the cold war, favoring the global from the regional front. With this conceptual change, it is possible to perceive the inflection on Brazil's international insertion.